2016
DOI: 10.1038/nrneurol.2016.166
|View full text |Cite
|
Sign up to set email alerts
|

The central vein sign and its clinical evaluation for the diagnosis of multiple sclerosis: a consensus statement from the North American Imaging in Multiple Sclerosis Cooperative

Abstract: At present, the diagnosis of multiple sclerosis (MS) relies heavily on the use of MRI, which can demonstrate disease dissemination in space and time [1][2][3][4] . The current 2010 McDonald criteria have enabled earlier diagnosis 5,6 and initiation of disease-modifying treatment, with substantial benefits for disease outcome 7,8 , but they still have imperfect sensitivity and specificity 9,10 . The limited accuracy of the criteria results in challenging cases and misdiagnosis, which are prevalent problems in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
351
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 314 publications
(367 citation statements)
references
References 61 publications
10
351
3
3
Order By: Relevance
“…Our analysis was limited to the brain and did not consider the spinal cord in the assessement of dissemination in space MRI criteria for MS. Of note, in vivo imaging reports of the central vein sign in the spinal cord are lacking, due in part to the challenge of obtaining high‐quality T2*‐weighted images of the cord 14. Patients with primarily confluent lesions were excluded from the study, and therefore it may not be possible to generalize our results to such patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis was limited to the brain and did not consider the spinal cord in the assessement of dissemination in space MRI criteria for MS. Of note, in vivo imaging reports of the central vein sign in the spinal cord are lacking, due in part to the challenge of obtaining high‐quality T2*‐weighted images of the cord 14. Patients with primarily confluent lesions were excluded from the study, and therefore it may not be possible to generalize our results to such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted with 3T and 7T MRI clearly showed that in MS, the association between brain WM venules and lesions (perivenular lesions), also named the “central vein sign,”17 can be efficiently visualized; in MS, the proportion of lesions that have clear central veins is high 14, 15. These data suggest that high frequency of perivenular lesions is pathologically specific to MS, and therefore this marker is an important candidate for improving MRI diagnostic criteria14 and for reducing the still too high rate of MS misdiagnosis, with its considerable clinical consequences 18, 19…”
mentioning
confidence: 99%
“…They are often localized in the anterior, deep WM, subcortical, juxtacortical brain regions, are rarely present in the infratentorial regions, and usually do not progress over time (13). In this context, the demonstration of the perivenular distribution within subclinical MS-like lesions can be particularly helpful (14).…”
Section: Ris and The Imperative Of Differential Diagnosismentioning
confidence: 99%
“…6 However, the presence of nonspecific WML, which increase with age and with certain risk factors, confounds a confirmatory diagnosis of MS. A number of studies have proposed perivenous WM lesion count (herein referenced as a percentage of total perivenous white matter lesion count [%PVWML]), as de-perivenous lesions has led to some uncertainty in evaluating %PVWML as an imaging biomarker. The recently published consensus statement by the North American Imaging in Multiple Sclerosis committee promotes a more controlled evaluation of the perivenous lesions 13 by suggesting several exclusion criteria in defining the central vein sign (CVS); specifically, the exclusion of lesions that are Ͻ3 mm in diameter in any plane, are confluent, have multiple distinct veins, or have poor visibility. Additionally, the consensus statement calls for the investigation of a standard radiologic definition of the CVS.…”
mentioning
confidence: 99%